Facilitating Transformative Experiences: Case studies for School Design - MackIntosh, Lara; Creagh, Robyn; McGann, Sarah (The Architectural Science Association, 2017)
Our rapidly changing world, current environmental crisis and calls for regenerative approaches to development evidences the need for change. To achieve sustainable change a transformation in the way we understand and conduct relationships in and with the world is required. The environment is not something at arm’s length, but rather a complex system, of which built, natural, and social systems, among others, are all part. As a profession architecture must have approaches that are reflexive, responsive, longitudinal and inclusive. This paper draws together two illustrative case studies to demonstrate such approaches. These case studies underscore the potential to facilitate continued transformation within approaches to the design of space and the discipline of architecture. The two workshops discussed in this paper enabled architects, teachers, policy-makers and others, to look at their own roles within the broader systems that shape the built environment of schools. Transformative learning is taken as a theoretical model through which to reflect on the two case studies. Transformative learning experiences are those that are most likely to prompt, support and sustain change in worldview and behaviour. They can be catalyst events that are uncommon, unusual or uncomfortable, and challenge assumptions and beliefs. This paper focuses on three aspects that modified the participants’ ability to engage more or less fully in the workshops as a transformative event. These aspects are discussed here as key factors which those seeking to develop events to help provoke change could use to guide workshop development and reflection. These three aspects are the role of unfamiliar context as provocation; agency as capacity and ability to change, and making connections to the everyday. These three aspects are discussed for their potential to contribute to transformation as part of the continuing development of the architecture profession.